Perencanaan Groundsill di Hilir Bendung Waikomo Kabupaten Lembata - NTT - Suhudi ST., MT.; Damianus Dai Tukan (Universitas Tribhuwana Tunggadewi Malang, 2018)
Waikomo weir located in Lembata Regency - East Nusa Tenggara is the only building on the river were built in 1972 and used to raise the water level Waikomo River to flow into the rice field of 1200 Ha. The length of Weir 40 m and height 1.50 m, was made of concrete. The condition of Waikomo weir todays has occurred crush depth 1.0 m downstream of the dam to 75.00 m further downstream and ruined retaining wall along the side of 7.00 m. The purpose of this research was to determine the cause of crush and how dimensions of groundsill building used to overcame the crushing and how stability groundsill planned to roll, shear and bearing capacity. Phase of this research includes observations, measurements in the field and collected secondary data from government instances. After used analysis cause of scour in the downstream weir, rainfall analysis, then continued with the Log Pearson Type III method. Once known discharge plans period return 50 years of 39.999 m3/sec, so did the design of groundsill measure and calculate the stability. The results showed that the cause of crush in the downstream weir is due to the mining Waikomo excavated material C by the local community. Groundsill planned height of 1.00 m, length 30.00 m, width 4.61 m, used energy absorbers pool type III and was located 75.00 m from Waikomo weir. From the calculations were known that groundsill plan safe to roll, moved and soil bearing capacity with a safety factor (SF) 1,5.